Bibliometric Analysis of Islamic Economics and Finance (IEF) Research on Indonesian Scopus Q1 Journals - As-Salafiyah, Aisyah; Rusydiana, Aam Slamet; Cahyono, Eko Fajar (Fara'id and Wealth Management, 2023)
In 2020, there were 4 Indonesian Scopus Q1 journals that examined sharia economics and finance, namely IJIMS, QIJIS, Studia Islamika and JII. Therefore, the purpose of this study is to present a bibliometric meta-analysis and visualization of the top trends of the theme articles from the Indonesian journal Scopus Q1. This study uses a journal database to analyze the percentage of the number of publications, the most widely used topics, the methodological approach, the top authors, the top agencies and the top countries where the research objects are located. Indonesia is the most influential country in the number of top article writers, top agencies and the most popular research object countries. The most widely published articles are QIJIS journals with a percentage of 42%, IJIMS with a percentage of 33%, Studia Islamika with a percentage of 17%, and JII with a percentage of 8%. This research can be used by readers to understand the general picture of sharia economic and financial article trends in the Indonesian Scopus Q1 journal and to know its contributors/authors, their institutions, the countries of their research and the topics they use.